2017
DOI: 10.3892/mmr.2017.6983
|View full text |Cite
|
Sign up to set email alerts
|

LPS enhances TLR4 expression and IFN-γ production via the TLR4/IRAK/NF-κB signaling pathway in rat pulmonary arterial smooth muscle cells

Abstract: The aim of the present study was to investigate the role of the Toll-like receptor (TLR)4 signaling pathway in cellular response to lipopolysaccharide (LPS) in rat pulmonary artery smooth muscle cells (PASMCs). Chronic obstructive pulmonary disease (COPD) rats were established with passive inhaling cigarette smoke plus injection of LPS. The TLR4 protein in lung tissues was determined with immunohistochemical staining and protein levels of the components of the TLR4 pathway in PASMCs were analyzed with western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 16 publications
3
41
0
Order By: Relevance
“…Monocytes circulate in blood and mature upon entering tissues where they receive local tissue signals that shape their phenotype . Mϕs are tissue‐resident leukocytes that exhibit an array of pattern recognition receptors (PRRs), which recognize a diverse collection of foreign invaders through sensing of non‐self‐molecular motifs called pathogen‐associated molecular patterns (PAMPs) . Upon activation of PRRs, communicational proteins (e.g., cytokines) are manufactured by the cell, cueing and mobilizing a repertoire of effector cells to the compromised locale (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes circulate in blood and mature upon entering tissues where they receive local tissue signals that shape their phenotype . Mϕs are tissue‐resident leukocytes that exhibit an array of pattern recognition receptors (PRRs), which recognize a diverse collection of foreign invaders through sensing of non‐self‐molecular motifs called pathogen‐associated molecular patterns (PAMPs) . Upon activation of PRRs, communicational proteins (e.g., cytokines) are manufactured by the cell, cueing and mobilizing a repertoire of effector cells to the compromised locale (Fig.…”
Section: Introductionmentioning
confidence: 99%
“… Illustration of broad communication and crosstalk among innate immune cells and signaling cascades . The success of innate immunity to recognize a diverse collection of foreign invaders relies on PRRs that sense non‐self‐molecular motifs (i.e., PAMPs) . Upon activation of PRRs, commonly characterized as Toll‐like receptors (TLRs), C‐type lectins (CLRs), retinoic acid‐inducible gene (RIG)‐I like receptors (RLRs), and nucleotide oligomerization domain (NOD)‐like receptors (NLRs), antimicrobial communicational proteins (e.g., cytokines) are manufactured by the cell .…”
Section: Introductionmentioning
confidence: 99%
“…TLR3 and TLR9 are considered as one of the important receptors of antiviral immunity. TLR signaling pathway involves many factors such as interferon regulatory factors (IRFs), IKK epsilon/TBK1, interferon regulatory factors (IRFs), and interferon (IFN) . Studies have shown that the activation of TLRs receptor can activate the immune signaling pathway of TLRs‐IKK epsilon‐IRFs‐IFN in host cells and induce immune inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…TLR signaling pathway involves many factors such as interferon regulatory factors (IRFs), IKK epsilon/TBK1, interferon regulatory factors (IRFs), and interferon (IFN). 5 Studies have shown that the activation of TLRs receptor can activate the immune signaling pathway of TLRs-IKK epsilon-IRFs-IFN in host cells and induce immune inflammation. The immune inflammatory factors produced can activate immune cells Th1, Th2, Th17, and Treg cells and produce immune cascade effect.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB, an important nuclear transcription factor, were activated by various inflammatory cytokines such as TGF-β1, TNF-α, and IL-1β. NF-κB activation can in turn promote the expression of inflammatory cytokines such as INF-γ, TGF-β1, TNF-α, and IL-1β [27,28]. A previous study showed that NF-κB activation occurred in the lungs of patients with ARDS and may contribute to the increased expression of immunoregulatory cytokines and other proinflammatory cytokines [29].…”
mentioning
confidence: 99%